Balaganjur Training to Foster Young Generation Spirit in Ulian Village | Pelatihan Balaganjur untuk Menumbuhkan Semangat Generasi Muda Di Desa Ulian - I Nengah Wirya Adnyana (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Ulian Village is located in the northern corner of the city of Bangli, to be precise, in the Kintamani District. The Kintamani region has its characteristics, where most people work as farmers. Likewise, most of the people in Uian Village also work as farmers. There is a lack of artistic movement figures in Ulian Village, which may make Ulian Village still sparse/less visible in the arts, especially in karawitan art. So from this, the authors implemented the KKNT Program in Ulian Village, which aims to provide more insight into the Ulian village community and to foster the enthusiasm of the younger generation through Balaganjur training in Ulian Village. So that from the problems that arise, the author provides general knowledge about the art of karawitan to the village community, especially in practicing appropriate techniques directly, providing percussion training, both adult seka gong and youth seka gong and the author will provide one percussion work the author is Tabuh Balaganjur Melasti. Through this KKNT Program, the authors can implement their knowledge and will positively impact the Ulian village community, increasing artistic creativity, especially in musical arts.